The Study of Effect Exercise Interval Circuit Training on Waist-hip Ratio - Natseeta, Onuma; Busara, Jaturabhuj (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purposes of the study were to evaluate the waist-to-hip circumference of the participants, who used the interval circuit training and to compare the waist-to-hip circumference before and after joining the interval circuit training. The target group was 7 institute staff who volunteered to the program and had a waist-to-hip circumference of more than 80-90 centimeters. Research instruments included 5-item questionnaires, waist and hip circumference record and a 10-week interval circuit training program. Data analyses were frequency, percentage, mean, and standard deviation. The hypothesis test by compared the mean of the waist-to-hip circumference before and after the training used t-test dependent. The results showed that Most of the samples were 5 female faculties with the average age of 37 years old having the exceed of circumference waist-to-hip above the 100 percent criterion standard. The aggregate waist-to-hip circumference before training was = .89, S.D = .07 and after training was = .85, S.D = .07. The results of the hypothesis test showed that the waist-to-hip circumference reduced after training for a statistically significant difference at .001. Participants were 100% satisfied on the highest level in all areas.